Monthly Distribution of Precipitation in Peninsular Malaysia - Camerlengo, Alejandro Livio; Saadon, Mohd Nasir; Aziz, Ahmad Shazli; Othman, Mohd Rosni (Universiti Putra Malaysia Press, 1998)
A study was made of the monthly distribution of rainfall in Peninsular Malaysia. It is shown that the principal influence is given by the passage of the Inter tropical Convergence Zone (ITCZ), while the secondary influence is the effects of both the NE and the SW monsoons